Symposium on the Futures of the Islamic World - Mahdi El-Mandjra (International Institute of Islamic Thought, 1993)
I am honored to be among such a distinguished group of people who have contributed so much to identifying the problems besetting the Islamic world. The subject under discussion highly strategic, especially at this time of sweeping upheaval and disruption that has been anticipated for years by future studies specialists. I thus have no illusions about the awesome task we face and am fully aware of the subject’s complexity. I have been working in the field of future studies for over twenty-five years and have participated in approximately two hundred international conferences and seminars related to this subject. This is the first time, I think, that an international symposium has been entirely devoted to the identification and analysis of current and anticipated problems as related to Islam. This is a sign of the maturity of the Islamic world, and similar initiatives must be encouraged in the future with the hope of initiating and supporting concrete research projects in this important am. Given the countries of origin of this symposium’s participants, I hope that its sponsors Will consider extending its activities beyond the scope of the Arab world. After all, Arabs are only 20 percent of the total Muslim population. When dealing with Islam, we must all beware of ethnocentric temptations, for Islam calls for a diversity that is conducive to unity. This prescription is enshrined in the Qur’an: 0 mankind! Lo! We have created you male and female, and have made you nations and tribes that ye may know one another. Lo! the noblest of you, in the sight of Allah, is the best in conduct. (49: 13) Accordingly, I consider this symposium to be a sort of rehearsal for other meetings to come and which will be more representative of the realities and potentialities of the Islamic world. We should therefore avoid the confusing generalization which has l&l the West to apply the specific reality of the Arab region to all countries of the Islamic world. This is not to be regarded as a critical stand against this symposium, but rather as an expression of a personal reservation concerning possible attempts to ...